International economic integration / edited by Ali M.EI Agraa - El-Agraa, Ali M. (ed.) (London, 1982)
International economic integration is defined as the act of two nations or more agreeing to pursue common aims and policies. Since the world contains numerous schemes of this nature there is a great need for a book which gives adequate discussion and coverage of all significant schemes. The aim of this book is to do precisely that in a brief and concise manner. It is therefore a unique book.
Keywords: International economic intgration